2021
DOI: 10.1088/1742-6596/1941/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on equity of health human resource allocation in Hubei Province based on the Gini coefficient and a HRDI model

Abstract: In order to fully understand the current situation of health human resources in Hubei Province, two mathematical models, Gini coefficient and health resource density index, were used to analyze the equity of health human resources in Hubei Province, and the Lorenz curve was drawn. After clarifying the distribution of four types of health technical personnel, the result showed that the fairness of distribution by population was better, and the fairness of distribution by geography area needed to be improved. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Foreign scholars have used statistical models to conduct empirical analyses on medical and health resources allocation [ 7 , 8 , 9 , 10 , 11 ]. The Gini coefficient was used to study medical and health resources allocation in the 1980s [ 12 , 13 , 14 ], and has been widely applied in the distribution of medical and health resources since then [ 15 , 16 , 17 , 18 , 19 , 20 ]. Limited to reflecting only the overall distribution, the Gini coefficient is often used in conjunction with other methods [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign scholars have used statistical models to conduct empirical analyses on medical and health resources allocation [ 7 , 8 , 9 , 10 , 11 ]. The Gini coefficient was used to study medical and health resources allocation in the 1980s [ 12 , 13 , 14 ], and has been widely applied in the distribution of medical and health resources since then [ 15 , 16 , 17 , 18 , 19 , 20 ]. Limited to reflecting only the overall distribution, the Gini coefficient is often used in conjunction with other methods [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BCC model can provide the relative efficiency and returns to scale among decision-making units. Based on the investigation of the efficiency of previous studies [6][7][8][9][10] , this paper calculates the utilization efficiency of health resources. The input indicators selected are the number of institutions, the number of beds and the number of health technicians, and the output indicators are the number of diagnosis and treatment (10000 times) and the number of inpatient surgeons.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…The COVID-19 pandemic has highlighted severe weaknesses in Chinese healthcare systems and a lack of focus on health resource allocation [7]. Previous research has shown that inequalities still exist in the state of health and the use of health services in China [8][9][10]. Guangxi Zhuang Autonomous Region is an ethnic frontier and economically underdeveloped.…”
Section: Introductionmentioning
confidence: 99%